2016
DOI: 10.1136/thoraxjnl-2015-208038
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sleep-disordered breathing and the risk of delivering small for gestational age infants: a prospective cohort study

Abstract: Objectively measured SDB in the third trimester is significantly associated with the delivery of SGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 42 publications
(49 reference statements)
2
72
0
Order By: Relevance
“…11,12 The 3D-Study recruited 2,366 women in their first trimester of pregnancy and their respective births across nine sites in the province of Quebec and gathered extensive data on the mother-father-child triad from conception until 2 years postpartum. At 2 years postpartum, children underwent cognitive, motor, and language testing using the Bayley Scales of Infant and Toddler Development, 3rd edition, and the MacArthur-Bates Communicative Development Our primary objective was to compare the neurodevelopment in children born with the help of fertility treatments (exposed) relative to those born off pregnancies conceived naturally (controls).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 The 3D-Study recruited 2,366 women in their first trimester of pregnancy and their respective births across nine sites in the province of Quebec and gathered extensive data on the mother-father-child triad from conception until 2 years postpartum. At 2 years postpartum, children underwent cognitive, motor, and language testing using the Bayley Scales of Infant and Toddler Development, 3rd edition, and the MacArthur-Bates Communicative Development Our primary objective was to compare the neurodevelopment in children born with the help of fertility treatments (exposed) relative to those born off pregnancies conceived naturally (controls).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to many symptom-based studies, several studies using objective measures of OSA have failed to find evidence of a link with PTB [23,48,49] although one study did find an increase in PTB (<37 weeks gestation and <32 weeks gestation) in women with OSA in a retrospective cohort [26]. Mean gestational age in women with OSA may be slightly shorter than controls 44 although a recent study has not been able to support these findings [47].…”
Section: Preterm Birthmentioning
confidence: 76%
“…Most studies that have longitudinally recruited women fail to find a relationship between maternal OSA and birth weight [46,47], SGA [46][47][48][49], or LGA [48]. Different polysomnographic systems were used across these studies and definitions of OSA varied by study.…”
Section: Sdb and Delivery Outcomesmentioning
confidence: 99%
“…Several recent studies indicate that snoring mothers are more likely to have SGA infants and exhibit higher risk for perinatal complications [88][89][90][91][92] . Furthermore, and as a validity preamble to the putative distal yet adverse role of OSA on the overall well-being of the offspring, we have shown that implementation and cholesterol levels were all significantly higher in gestationally-exposed male offspring at 24 weeks of age (corresponding to mid adulthood in human) but not in exposed female offspring 98,99 .…”
Section: Obstructive Sleep Apnoea During Pregnancy and Consequences Tmentioning
confidence: 99%